Customer’s perception towards green marketing in Kathmandu Valley - Bhattarai, Tanil (Nepalese Journal of Management, 2024)
This study examines the factors influencing customer perception towards green marketing in Kathmandu Valley. Customer’s perception is the dependent variable. The selected independent variables are eco-brand, eco-labeling, green advertisement, green packaging, environmental awareness and green product value. The primary source of data is used to assess the opinions of the respondents regarding customer’s perception towards green marketing in Kathmandu Valley. The study is based on primary data with 143 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of eco-brand, eco-labeling, green advertisement, green packaging, environmental awareness and green product value on customer’s perception towards green marketing in Kathmandu Valley. This results showed that green packaging has a positive impact on customer’s perception towards green marketing. This indicates that green packaging of products stimulates the customer’s perception towards green marketing. Likewise, eco-labelling has a positive impact on customer’s perception for green marketing. It indicates that increase in eco- labeling directs customer’s perception towards green marketing. Furthermore, green product value has a positive impact on customer’s perception for green marketing. It reveals that green product value stimulates customer’s perception towards green marketing. Similarly, green advertisement has a positive impact on customer’s perception for green marketing. It means that green advertisement drives customer’s perception for green marketing. Similarly, eco-brand has a positive impact on customer’s perception towards green marketing. It means that eco-brand stimulates customer’s perception towards green marketing. In addition, environmental awareness has a positive impact on customer’s perception for green marketing. It means that products concerning environmental awareness drives customer’s perception towards green marketing.